Race talk and the conspiracy of silence : understanding and facilitating difficult dialogues on race - Sue, Derald Wing. (Hoboken, New Jersey : Wiley, 2015)
"Learn to talk about race openly, honestly, and productivelyMost people avoid discussion of race-related topics because of the strong emotions and feelings of discomfort that inevitably accompany such conversations. Rather than endure the conflict of racial realities, many people choose instead to avoid the topic altogether, or remain silent when it is raised. Race Talk and the Conspiracy of Silence: Understanding and Facilitating Difficult Dialogues on Race puts an end to that dynamic by sharing strategies for smoothing conversations about race in a productive manner.A guide for facilitating and participating in difficult dialogues about race, author Derald Wing Sue - an internationally recognized expert on multiculturalism, diversity, and microaggressions - explores the characteristics, dynamics, and meaning behind discussions about race as well as the hidden "ground rules" that inhibit honest and productive dialogue. Through emotional and visceral examples, this book explains why conversations revolving around racial issues are so difficult, and provides guidelines, techniques, and advice for navigating and leading honest and forthright discussions. Readers will develop a stronger ability to build rapport with people unlike themselves, and discover how not talking about race impacts society as a whole. Overcome and make visible the fears associated with race talk Learn practical ideas for talking openly about race Facilitate and navigate discussion with expert strategy Examine the hidden rules that govern race talk Understand the benefits of successful conversations Discussions about race do not have to result in disastrous consequences, and can in fact be highly beneficial to all parties involved. It's important that people have the ability to converse openly and honestly with their students, colleagues, children, and neighbors, and Race Talk provides the path for achieving this goal"--
What is Race Talk? -- The Characteristics and Dynamics of Race Talk -- The Stories We Tell: White Talk vs. Back Talk -- "The Entire World's a Stage!" -- Colorblind Means Colormute -- "What are the Consequences for Saying What I Mean?" -- "To Speak or How to Speak, that is the Question." -- "I'm Not Racist!" -- "I'm Not White, I'm Italian!" -- Interracial/Interethnic Race Talk: Difficult Dialogues between Groups of Color -- Race Talk and White Racial Identity Development: For Whites Only -- Being an Agent of Change: Guidelines for Educators, Parents, and Trainers -- Helping People Talk About Race: Facilitation Skills for Educators and Trainers.
Includes bibliographic references (pages 245-259) and index.
Keywords: Social psychology; Racism in education; Multicultural education